THROWING SPAGHETTI, SEEING WHAT STICKS: ITERATIVE DECEPTION IN DIGITAL STRATEGIC INFORMATION OPERATIONS - Marino, Giada; Giglietto, Fabio; Chakraborty, Anwesha; Terenzi, Massimo; Olaniran, Samuel (AoIR Selected Papers of Internet Research, 2026)
This study examines the strategic exploitation of social media platforms, particularly Facebook, for information operations that extend beyond traditional disinformation. These operations employ a range of misleading content and tactics to maximize reach and influence, compromising the integrity of digital spaces. Using a mixed-methods approach grounded in the theoretical framework of strategic information operations, the study analyzes the intersection of algorithmic affordances, deceptive tactics, and user-driven amplification dynamics. The research focuses on three case studies: pro-Putin propaganda, online casino promotion, and the spread of adult content in poorly moderated groups. These cases illustrate how malicious actors leverage Facebook’s platform features to conduct strategic information operations, manipulating public discourse and increasing the perceived influence of deceptive narratives. The study reveals how these operations blend political and benign content to fabricate grassroots support, use automated tools to maintain visibility and exploit weak moderation policies to disseminate illicit content. The findings highlight significant governance and policy implications, emphasizing the need for robust strategies to mitigate these operations. The research also addresses challenges posed by restricted access to social media data and calls for greater investment in accessible monitoring tools and transparent data-sharing mechanisms. The presentation will discuss these case studies in the context of current social media governance, underscoring the critical need for enhanced monitoring tools to combat deceptive information operations.